DOK6 promoter methylation serves as a potential biomarker affecting prognosis in de novo acute myeloid leukemia. (4th September 2019) - Sun, Guo‐Kang; Tang, Li‐Juan; Zhou, Jing‐Dong; Xu, Zi‐Jun; Yang, Lan; Yuan, Qian; Ma, Ji‐Chun; Liu, Xing‐Hui; Lin, Jiang; Qian, Jun; Yao, Dong‐Ming
Abstract: Background: Downstream of tyrosine kinase 6 ( DOK6 ), which is specifically expressed in the nervous system, was previously recognized as an adapter only in neurite outgrowth. Recent studies also demonstrated the potential role of DOK6 in solid tumors such as gastric cancer and breast cancer. However, previous studies of DOK6 have not dealt with its roles in myeloid malignancies. Herein, we verified the promoter methylation status of DOK6 and further explored its clinical implication in de novo acute myeloid leukemia (AML). Methods: A total of 100 newly diagnosed adult AML patients were involved in the current study. DOK6 expression and methylation were detected by real‐time qPCR and methylation‐specific PCR (MSP), respectively. Bisulfite sequencing PCR (BSP) was performed to assess the methylation density of the DOK6 promoter. Results: Downstream of tyrosine kinase 6 promoter methylation was significantly increased in AML patients compared to controls ( P = .037), whereas DOK6 expression significantly decreased in AML patients ( P < .001). The expression of DOK6 was markedly up‐regulated after treated by 5‐aza‐2′‐deoxycytidine (5‐aza‐dC) in THP‐1 cell lines. The methylation status of the DOK6 promoter was associated with French‐American‐British classifications ( P = .037). There was no significant correlation existed between DOK6 expression and its promoter methylation ( R = .077, P = .635). Interestingly, of whole‐AML and non‐APL AML patients, both have a tendency pertaining to the DOK6 methylation group and a significantly longer overall survival (OS) than the DOK6 unmethylation group ( P = .042 and .036, respectively). Conclusion: Our study suggested that DOK6 promoter hypermethylation was a common molecular event in de novo AML patients. Remarkably, DOK6 promoter methylation could serve as an independent and integrated prognostic biomarker not only in non‐APL AML patients but also in AML patients who are less than 60 years old. Abstract : DOK6; Methylation; AML.